2008
DOI: 10.1111/j.1467-9701.2008.01140.x
|View full text |Cite
|
Sign up to set email alerts
|

The Determinants of GATS Commitment Coverage

Abstract: This paper investigates hypotheses about the determinants of trade and investment liberalisation with a particular focus on the market access and national treatment commitments under the General Agreement on Trade in Services (GATS). We set up a database of these GATS commitments and use the ratio of all commitments listed by a country to the possible number of commitments as a measure of liberalisation of market access/national treatment. Our empirical analysis suggests that larger and 'richer' countries comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 30 publications
(43 reference statements)
0
14
0
Order By: Relevance
“…Research on this has concluded that variables such as per capita income and market size are correlated with more extensive commitments (Hoekman, 1996) but there is little support for endowment-based predictions of the overall depth and coverage of commitments (Roy, 2009). Egger and Lanz (2008) argue that theory suggests that countries that are capital scarce should make more commitments because the potential gains from trade (liberalization) are largest for such nations, but conclude that the evidence is not supportive of this hypothesis. Analysis of the determinants of commitments is more complex than for goods (the GATT) because of the need to explicitly consider the multiple modes through which trade can occur and map this to the endowments (comparative advantage) of countries.…”
mentioning
confidence: 61%
“…Research on this has concluded that variables such as per capita income and market size are correlated with more extensive commitments (Hoekman, 1996) but there is little support for endowment-based predictions of the overall depth and coverage of commitments (Roy, 2009). Egger and Lanz (2008) argue that theory suggests that countries that are capital scarce should make more commitments because the potential gains from trade (liberalization) are largest for such nations, but conclude that the evidence is not supportive of this hypothesis. Analysis of the determinants of commitments is more complex than for goods (the GATT) because of the need to explicitly consider the multiple modes through which trade can occur and map this to the endowments (comparative advantage) of countries.…”
mentioning
confidence: 61%
“…In essence, these authors find that larger, more similarly sized countries with lower trade costs in the absence of political barriers to trade conclude trade-related PEIAs (mostly GTAs) more likely, and that such agreements have the intended stimulating effect on trade. While, at this point, there is less systematic evidence about the causes and consequences of STAs, it seems that liberalization of services trade is driven by the same factors and in a similar way as goods trade liberalization (see Egger and Lanz, 2008;Francois and Hoekman, 2010).…”
Section: An Eclectic Literature Reviewmentioning
confidence: 99%
“…6 Egger and Shingal (2013) examine the role of regulation in services trade as an EIA determinant. Furthermore, Egger and Lanz (2008) …nd that large countries and countries involved in FTAs have a higher relative GATS commitment coverage. This indicates that the decision to sign a trade agreement covering services may depend on the decision to have signed a trade agreement covering goods.…”
Section: Related Literaturementioning
confidence: 99%